2022
DOI: 10.1063/5.0110318
|View full text |Cite
|
Sign up to set email alerts
|

Absolute N-atom density measurement in an Ar/N2 micro-hollow cathode discharge jet by means of ns-two-photon absorption laser-induced fluorescence

Abstract: In this work, nanosecond two-photon absorption laser-induced fluorescence (TALIF) is used to probe the absolute density of nitrogen atoms in a plasma generated using a micro-hollow cathode discharge (MHCD). The MHCD is operated in the normal regime, and the plasma is ignited in an Ar/N2 gas mixture. First, we study a MHCD configuration having the same pressure (50 mbar) on both sides of the electrodes. A good agreement is found between the density of N atoms measured using TALIF in this work and previous measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Previous studies of the MHCD [8,17] showed that atomic nitrogen is produced inside the MHCD hole and can be transported over long distances (several cm) using a pressure differential. In this study, a substrate is placed in front of the MHCD and we measure the spatial N atoms density profile.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies of the MHCD [8,17] showed that atomic nitrogen is produced inside the MHCD hole and can be transported over long distances (several cm) using a pressure differential. In this study, a substrate is placed in front of the MHCD and we measure the spatial N atoms density profile.…”
Section: Resultsmentioning
confidence: 99%
“…The fluorescence emitted by the laser-excited atomic state in the plasma is collected perpendicularly to the laser beam, using a 10-cm-focal-length lens, in a 4f configuration, and a photomultiplier tube. A complete description of the experimental TALIF setup used, and thorough validity verification can be found in Remigy et al [17].…”
Section: Talif Diagnostic Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of APPJ are influenced by discharge configuration, working gas, and driving scheme. Typical APPJs are generated by needle electrode, dielectric barrier discharge or micro-hollow cathode configuration within gas He/Ar [1,[6][7][8]. Some temporal evolution photographs of the plasma jet obtained by intensified charge-coupled device (ICCD) camera show that a continuous plasma jet observed by the naked eye is actually composed of a moving plasma bullet or a guided ionization wave [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The discharge is sustained by electrons undergoing a pendulum motion inside the HC [2][3][4][5][6][7]. Hollow cathode discharges are employed in many applications, e.g., in atomic spectroscopy [1, [8][9][10], mass spectrometry [11], and laser technology [12], as UV generators [13,14] and propulsion thrusters [15,16], for the generation of neutral and ion beams [17,18], surface processing [19], thin film deposition [20][21][22][23][24][25][26][27], and in plasma chemical investigations [28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%